Breast and cervical cancer screening for risk assessment in Cambodian women. (2nd April 2020) - Vorn, Rany; Ryu, Eunjung; Srun, Sreynet; Chang, Soonbok; Suh, Insoo; Kim, Woojung
Abstract: The estimated mortality rates for breast and cervical cancer in Cambodia are high, perhaps because the Cambodian population lacks information about their detection and prevention. This cross-sectional study assessed the distribution of cervical cancers among and the behavioural and clinical characteristics of Cambodian women. It comprised 1039 Cambodian women who were interviewed between August 2013 and January 2016; the interviews were conducted in person using structured questionnaires. Among the participants, 801 (77.2%) and 709 (68.3%) had heard of cervical cancer and cervical cancer detection tests, respectively. However, 830 (80.2%) had never undergone a Pap smear, and 633 (60.9%) had never heard of breast self-examination. Despite the high mortality rates for breast and cervical cancer in Cambodia, only a small percentage of the participants had risk factors (e.g. smoking, alcohol consumption) for female cancers. A nationwide survey of the knowledge, attitudes and practices related to female cancers is recommended. Impact Statement: What is already known on this subject? The estimated incidence and mortality rates of breast and cervical cancers in Cambodia are high. How much Cambodian women know about these cancers and whether they are receptive to cancer screening are questions requiring further study. What do the results of this study add ? To our knowledge, this is the first study to describe the female cancer-related behavioural and clinical characteristics of Cambodian women. We show that rural Cambodian women are mostly unaware of breast and cervical cancer screening and that only a small percentage had risk factors for these cancers, despite the high incidence of these cancers in Cambodia. What are the implications of these findings for clinical practice and/or further research? Our findings potentially aid the design of programmes that increase awareness of breast and cervical cancers in Cambodia. Such programmes would be expected to reduce the incidence and mortality rates of these cancers in this country. Nationwide screening programmes for female cancers should be implemented in Cambodia.